Respuesta :

Answer:

*In Explanation

Step-by-step explanation:

1) Start by just substituting the value of x (given in equation 1) into the second equation:

y = 3x - 1

y = 3(2) - 1

y = 6-1 = 5

2) Since both equations have x on one side, make both equations equal to one another:

2y + 4 = 9 - 3y

Solve for y:

5y = 5

y = 1

Plug y = 1 into either one of the given equations and solve for x:

I'll use first equation:

x = 2y + 4

x = 2(1) + 4

x = 6

3) When substituting X into the second equation, remember to use parenthesis:

The student was substituting x from equation 1 into equation 2, but they forgot to multiply ALL of 2y + 3 by 2.

x = 2y + 3

Substitute into 2nd eqn:

y = 2(2y + 3) - 9

ACCESS MORE